2003
DOI: 10.1034/j.1600-0609.2003.00047.x
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme replacement therapy reduces Gaucher cell burden but may accelerate osteopenia in patients with type I disease – a histological study

Abstract: Enzyme replacement treatment (ERT) is effective in controlling the clinical and biochemical manifestation of type I Gaucher disease. Little is known on the evolution of bone marrow histology caused by ERT. We compared the pretreatment trephine bone marrow biopsies in five patients (F32, F41, F50, M55, and M46) with the control biopsies performed after 26-32 months of imiglucerase treatment. The planimetric estimates revealed significant decrease in Gaucher cell burden in all the patients. The post-ERT values r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 28 publications
1
12
0
5
Order By: Relevance
“…As for the relationship between ERT and GC, it is suggested here that ERT represents prevention of GC induction by its positive influence on monocytes able to endocytose effectively the applied enzyme (Sato and Beutler 1993). This is in accord with the observation of decreased number of GCs during ERT (Rudzki et al 2003). The effect of ERT on the monocyte-histiocytic lineage could thus be better evaluated by measuring the increasing proportion of nonstorage macrophages.…”
Section: Enzyme Replacement Therapy (Ert)supporting
confidence: 60%
“…As for the relationship between ERT and GC, it is suggested here that ERT represents prevention of GC induction by its positive influence on monocytes able to endocytose effectively the applied enzyme (Sato and Beutler 1993). This is in accord with the observation of decreased number of GCs during ERT (Rudzki et al 2003). The effect of ERT on the monocyte-histiocytic lineage could thus be better evaluated by measuring the increasing proportion of nonstorage macrophages.…”
Section: Enzyme Replacement Therapy (Ert)supporting
confidence: 60%
“…In correlation with the reduction of bone symptoms, ERT has been shown to have a significant positive effect on the quality of life of GD patients with skeletal disease after 2 years of treatment [101]. Finally, Rudzki et al [101] evaluated also bone marrow biopsies prior to and after 26-32 months of ERT.…”
Section: Imiglucerasementioning
confidence: 99%
“…Finally, Rudzki et al [101] evaluated also bone marrow biopsies prior to and after 26-32 months of ERT. The effect was mainly achieved by the reduction of Gaucher cell burden, the disappearance of Gaucher cells, and, but only partially, by the shrinkage of Gaucher cells.…”
Section: Imiglucerasementioning
confidence: 99%
“…15,16 Recent data have shown both bone marrow and hematopoietic abnormalities in GD, and bone marrow infiltration by Gaucher cells was observed in GD patients. [17][18][19][20] It has also been reported that GD may affect the growth of erythroid progenitors and myelopoiesis of induced pluripotent stem cells (iPSCs). 21 Moreover, an important extramedullary hematopoiesis with the presence of erythroid cells was observed in the spleen of a murine model of GD.…”
Section: Introductionmentioning
confidence: 99%